2018
DOI: 10.1007/s40520-018-1012-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high-intensity interval training on glycemic control and cardiorespiratory fitness in patients with type 2 diabetes: a systematic review and meta-analysis

Abstract: Aims The aim of this systematic review and meta-analysis was to quantify the effect of high-intensity interval training (HIIT) on glycemic control and cardiorespiratory fitness compared with moderate-intensity training (MICT) and no training at all in patients with type 2 diabetes (T2D). Methods Relevant articles were sourced from PubMed, Embase, the Web of Science, EBSCO, and the Cochrane Library. Randomized-controlled trials were included based upon the following criteria: participants were clinically diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 49 publications
7
68
2
3
Order By: Relevance
“…Exercise is considered a cornerstone in the treatment of type 2 diabetes (T2D), and moderate‐intensity continuous training (MICT) can lower HbA1c, reduce fat mass and increase maximum oxygen uptake (V˙O 2 max) . In recent years, meta‐analysis studies have concluded that high‐intensity interval training (HIIT) is superior to MICT in improving glycaemic control in patients with T2D . HIIT is characterized by a high aerobic load, whereas sprint interval training (SIT) is characterized by a high anaerobic load, consisting of short (10–30 seconds) all‐out sprints interspersed by long (2‐4 minute) recovery periods.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is considered a cornerstone in the treatment of type 2 diabetes (T2D), and moderate‐intensity continuous training (MICT) can lower HbA1c, reduce fat mass and increase maximum oxygen uptake (V˙O 2 max) . In recent years, meta‐analysis studies have concluded that high‐intensity interval training (HIIT) is superior to MICT in improving glycaemic control in patients with T2D . HIIT is characterized by a high aerobic load, whereas sprint interval training (SIT) is characterized by a high anaerobic load, consisting of short (10–30 seconds) all‐out sprints interspersed by long (2‐4 minute) recovery periods.…”
Section: Introductionmentioning
confidence: 99%
“…The American Diabetes Association recommends at least 150 minutes of moderate‐intensity or vigorous exercise per week for T2D management, although a meta‐analysis by Umpierre et al indicates that exercising more than 150 minutes per week leads to a greater decline in hemoglobin A 1C compared with exercise of 150 minutes or less per week. Moreover, two recent meta‐analyses conclude that HIIE provides similar or greater benefits than moderate‐intensity continuous exercise to patients with T2D . Based on these outcomes, we constructed a prolonged exercise protocol including high‐intensity intermittent periods.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two recent meta-analyses conclude that HIIE provides similar or greater benefits than moderate-intensity continuous exercise to patients with T2D. 4,5 Based on these outcomes, we constructed a prolonged exercise protocol including high-intensity intermittent periods. Consistent with our protocol, Nadeau 28 proposes 45-60 minutes of aerobic exercise (preferably HIIE) per day for managing T2D, while Sari-Sarraf et al 29 applied a combined continuous and interval aerobic exercise protocol lasting 54 minutes on patients with metabolic syndrome (most of whom suffered from T2D) for 16 weeks, resulting in a plethora of positive clinical effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations